2019
DOI: 10.1108/cr-08-2018-0050
|View full text |Cite
|
Sign up to set email alerts
|

The significance of proximityin cluster initiatives

Abstract: Purpose The purpose of this paper is to analyse relations between geographical and competence proximity and development of cooperation in cluster initiatives. Design/methodology/approach The research was based on an original theoretical concept referring to the trajectory of the development of cooperative relations in cluster initiatives. The research was carried out in mid-2017, in four purposefully selected cluster initiatives. The research sample was 132 cluster enterprises. The main research strategy inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…Based on the research conducted in selected cluster organisations, it has been established that cooperation in COs can take different forms, which separated into sets, can form a hierarchical system consisting of four levels of cooperation: level I "Integration at the unit level", level II "Allocation and integration at the process level", level III "Impact on the environment" and level IV "Creation and integration at the organisational level" (Lis, 2018(Lis, , 2019. As the research survey indicates, despite the differences among the four stages of development of cooperative relationships, cluster organisations may assume three fundamental roles at each stage: of a direct resource supplier, a broker and an integrator.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the research conducted in selected cluster organisations, it has been established that cooperation in COs can take different forms, which separated into sets, can form a hierarchical system consisting of four levels of cooperation: level I "Integration at the unit level", level II "Allocation and integration at the process level", level III "Impact on the environment" and level IV "Creation and integration at the organisational level" (Lis, 2018(Lis, , 2019. As the research survey indicates, despite the differences among the four stages of development of cooperative relationships, cluster organisations may assume three fundamental roles at each stage: of a direct resource supplier, a broker and an integrator.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, in order to fully use the services provided by institutions (e.g., technological institutes, universities, or business associations) in their innovation processes, there should be greater interaction between institutions and companies 15 , and institutions should speak the language of companies and meet their needs. In other words, strong cluster initiatives are required (Freije, 2015;Lis, 2019) to reinforce the associative networking of the textile sector and thus avoid the "uncoordinated dance" in which it seems to be immersed.…”
Section: Discussionmentioning
confidence: 99%
“…As far as a regional competence is based on common knowledge that allows different organisations to coevolve, one particular competence -the capacity to cooperate -is considered the contingent upon the interaction within the multiagent setting. Different firms participating in the regional cluster have different aims and divergent systems of preferences; however, the cooperation is available on the basis of some harmonised aims (Lis, 2018(Lis, , 2019. Problem solving actions within a group of interrelated organisations is based on the set of competences available to individual firms.…”
Section: Evolutionary Economics (Firm-level Ontogenetic Evolution)mentioning
confidence: 99%
“…The choice of a cluster and park structures for the study was affected by the similarities observed between them. Cluster organisations, also named cluster initiatives (Sölvell et al, 2003;Lindqvist et al, 2013;Štverková & Mynarzová, 2017;Lis, 2018Lis, , 2019, are understood as formally established organisations, functioning at a higher level of aggregation, composed of institutional members that consciously joined them (Lis, 2018). With regard to park structures, they are organisations that support the development of entities located in them, especially in the area of innovation and technology transfer.…”
Section: Introductionmentioning
confidence: 99%